Modeling the Revolving Revolution: The Debt Collection Channel - Drozd, Lukasz A.; Serrano-Padial, Ricardo (American Economic Review, 2017)
We investigate the role of information technology (IT) in the collection of delinquent consumer debt. We argue that the widespread adoption of IT by the debt collection industry in the 1990s contributed to the observed expansion of unsecured risky lending such as credit cards. Our model stresses the importance of delinquency and private information about borrower solvency. The prevalence of delinquency implies that the costs of debt collection must be borne by lenders to sustain incentives to repay debt. IT mitigates informational asymmetries, allowing lenders to concentrate collection efforts on delinquent borrowers who are more likely to repay. (JEL D14, D82, G21, L84, M15, O33)